Asian management systems : - Chen, Min (Routledge, 1995)
This volume looks at four main management systems in the East Asian region: Japanese, mainland Chinese, overseas Chinese and Korean. Through a comparative analysis of organizational structures, competitive strategies and cultural influences the workings of each system is made clear. Practical guidelines make this book a vital guide for international executives and students alike.